Social geographies from difference to action - Panelli, Ruth (SAGE, 2004)
This accessible textbook is a stimulating introduction to contemporary social geography. It provides students with the tools to understand the various frameworks that geographers use to conceptualize, document, and attempt to overcome social differences.